Facilitation of Dye-Based Quantitative Real-Time Polymerase Chain Reaction with Poly(ethylene glycol)-Engrafted Graphene Oxide - Khushbu Chauhan; Dong-Min Kim; Eunbin Cho; Dong-Eun Kim (Nanomaterials, 2023)
Quantitative real-time polymerase chain reaction (qPCR) is an important and extensively utilized technique in medical and biotechnological applications. qPCR enables the real-time detection of nucleic acid during amplification, thus surpassing the necessity of post-amplification gel electrophoresis for amplicon detection. Despite being widely employed in molecular diagnostics, qPCR exhibits limitations attributed to nonspecific DNA amplification that compromises the efficiency and fidelity of qPCR. Herein, we demonstrate that poly(ethylene glycol)-engrafted nanosized graphene oxide (PEG-nGO) can significantly improve the efficiency and specificity of qPCR by adsorbing single-stranded DNA (ssDNA) without affecting the fluorescence of double-stranded DNA binding dye during DNA amplification. PEG-nGO adsorbs surplus ssDNA primers in the initial phase of PCR, having lower concentrations of DNA amplicons and thus minimizing the nonspecific annealing of ssDNA and false amplification due to primer dimerization and erroneous priming. As compared to conventional qPCR, the addition of PEG-nGO and the DNA binding dye, EvaGreen, in the qPCR setup (dubbed as PENGO-qPCR) significantly enhances the specificity and sensitivity of DNA amplification by preferential adsorption of ssDNA without inhibiting DNA polymerase activity. The PENGO-qPCR system for detection of influenza viral RNA exhibited a 67-fold higher sensitivity than the conventional qPCR setup. Thus, the performance of a qPCR can be greatly enhanced by adding PEG-nGO as a PCR enhancer as well as EvaGreen as a DNA binding dye to the qPCR mixture, which exhibits a significantly improved sensitivity of the qPCR.